Kinerja Dinas Perumahan Kawasan Permukiman Dan Penataan Ruang Dalam Pelaksanaan Program Rehabilitasi Rumah Tidak Layak Huni (R-RTLH) Di Kelurahan Sunggal Kota Medan - Novi Yanti Nur; Asima Yanty Sylvania Siahaan (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The performance of public organizations is always considered by the wider community, public organizations must have good service performance in order to have public trust. This study aims to identify and describe the performance of the Residential Area Housing and Spatial Planning Service in the Implementation of the Uninhabitable House Rehabilitation Program (R-RTLH) in Sunggal Village, Medan City. The method used in this research is descriptive research method with a qualitative approach. Data collection techniques were carried out by means of interviews, observation and documentation. The results of the study show that the performance of the Medan City Residential and Spatial Planning Office in the Implementation of the Uninhabitable House Rehabilitation Program (R-RTLH) has been running quite optimally, but is still constrained by limited human resources, funding sources and also lack of socialization. still closed. The productivity indicator for program implementation has reached 100% in the first six years, but in 2020 it could only reach 25.45% and in 2021 it was 68.29%. The quality of services provided has followed established procedures. Then the Medan City PKPPR Office has been responsive in understanding what the needs of the people who receive assistance from the Uninhabitable House Rehabilitation program. Responsibility has been seen from the suitability of the activities carried out with the legal basis that has been made in carrying out activities. Accountability already refers to the implementing guidelines that have been established with fairly accountable services.